Effectiveness of Chronic Disease Management Program in Lowering Blood Pressure in Hypertensive Patients: Literature Review - Akbar, Muhammad Alief; Wahid, Syarifuddin; Lestari, Indah; Adnan, Endy; Indarwati, Rezky Putri (Journal La Medihealtico, 2024)
Chronic illnesses are a global health issue that kills people. Hypertension is a blood vessel disorder that compromises the body's tissues' oxygen and nutrient supply. In 2025, 1.5 billion people will have hypertension, and 9.4 million will die from it. This research review evaluates the Chronic Disease Management Program's blood pressure-lowering effects in hypertensive patients. A PRISMA Flow Diagram-based literature review. Downloading scientific papers from PubMed, Portal Garuda, and Google Scholar follows SINTA IV and V criteria. This article searches for Prolanis, blood pressure, and hypertension. Search results yielded 103 articles. Using inclusion criteria, 11 research publications were chosen for review. The study found that the chronic disease management program, which included medical consultations, Prolanis participant education, SMS gateway reminders, home visits, club activities (exercise), and health status monitoring, effectively lowered blood pressure in hypertension patients.